Omega, Sadhana, Theta, and PI Polynomials of Double Benzonoid Chain - Fozia Bashir Farooq; Saima Parveen; Nadeem Ul Hassan Awan; Rakotondrajao Fanja (Journal of Mathematics)
Counting polynomials are closely related to certain features of chemical graphs and provide an elegant means of expressing graph topological invariants. The current paper aims to calculate four polynomials for double benzenoid chains, Sadhana, omega, theta, and Padmakar–Ivan (PI). The edge-cut method is used to derive analytical closed expressions for these polynomials.